Pharmacokinetics and pharmacodynamics of doxycycline in a Streptococcusequi subsp. zooepidemicus infection model in horses. Issue 5 (31st May 2021) - Chapuis, Ronan J. J.; Smith, Joe S.; Uehlinger, Fabienne D.; Meachem, Melissa; Johnson, Ron; Dowling, Patricia M.
Abstract: The objectives of this study were to investigate the pharmacokinetics (PK), pharmacodynamics (PD), and the efficacy of oral administration of doxycycline (DXC) in horses with Streptococcus zooepidemicus tissue infections. Tissue chambers (TC) were implanted subcutaneously in the cervical region of 7 horses and inoculated with a single S . zooepidemicus isolate with a minimum inhibitory concentration (MIC) of 0.25 µg/ml, determined by agar dilution. Doxycycline hyclate (10 mg/kg, orally, q 12 h, for 5 days) mixed with poloxamer gel was started following inoculation. The TC fluid was sampled prior to and following inoculation for cytology analysis, quantitative culture, and DXC determination. Plasma DXC concentrations were measured over 48 h following the last dose of DXC administered. The mean plasma peak concentration ( C max ) of DXC was 0.32 µg/ml, and concentrations above the MIC were only reached in 3 TC samples. In plasma, mean T > MIC was 2.4 h, mean C max /MIC was 1.30, and mean AUClast /MIC was 11.63 h. These PK/PD indices did not reach the suggested targets for DXC treatments of infections, and the TC abscessed in all horses. This is the first study to evaluate the recommended dose of DXC in horse in an infection model.